Pengembangan Ekowisata Bahari Berkelanjutan: Strategi Pengelolaan Lingkungan di Labuan Amuk, Karangasem - Magnus Nazarius; Mutiara Azzahra; Mariya Takerbak; Yulia Priska Solossa; Arto Suprapto; Dewa Kiskenda (Jurnal Ilmiah Ilmu Pariwisata, 2025)
ABSTRACT Ecotourism of Labuan Amuk is encouraging number of tourist visits which are still considered suboptimal. The aim of this study discusses the existing conditions and examines the strengths and weaknesses as well as opportunities and threats to formulate strategies and programs for developing ecological tourism as sustainable tourism in Labuan Amuk, Antiga optimally. A quantitative and qualitative approach used. Data collection was carried out through observation, in-depth interviews and questionnaires of 15 tourists visiting Labuan Amuk; the community, and tourism business actors (private) in Labuan Amuk. Data analysis was carried out using the SWOT method. Based on the SWOT analysis, alternative strategies were obtained that can be applied to the management of Labuan Amuk Ecotourism, namely (1) Strategy for creating and developing Sustainable Marine Ecotourism products; (2) Strategy for increasing Competitiveness through Digitalization and Diversification of the Tourism Economy; (3) Strategy for Optimizing Infrastructure and Environmentally Friendly Tourism Facilities; (4) strategy for strengthening the distribution channels for marketing ecotourism products to tourists staying in villas and tourist attractions in Labuan Amuk and its surroundings.. Ekowisata Labuan Amuk sedang mendorong jumlah kunjungan wisatawan yang masih dianggap belum optimal. Penelitian ini membahas kondisi eksisting serta mengkaji kekuatan dan kelemahan sekaligus peluang dan ancaman untuk merumusakan strategi dan program pengembangan wisata ekologis sebagai wisata berkelanjutan Labuan Amuk, Antiga secara optimal. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif. Pengumpulan data dilakukan dengan observasi, wawancara mendalam serta kuesioner terhadap 15 wisatawan yang berkunjung ke Labuhan Amuk; masyarakat, serta pelaku bisnis pariwisata (swasta) di Labuhan Amuk. Analisis data dilakukan dengan metode SWOT. Berdasarkan atas analisis SWOT diperoleh alternatif- alternatif strategi yang dapat diterapkan pada pengelolaan Ekowisata Labuan Amuk yaitu (1) Strategi menciptakan dan mengembangkan produk Ekowisata Bahari Berkelanjutan; (2) Strategi peningkatan Daya Saing Melalui Digitalisasi dan Diversifikasi Ekonomi Wisata; (3) Strategi Optimalisasi Infrastruktur dan Fasilitas Wisata Ramah Lingkungan; (4) strategi penguatan saluran distribusi pemasaran produk ekowisata kepada wisatawan yang menginap di villa-villa dan daya tarik wisata yang ada di Labuan Amuk dan sekitarnya.